2000
DOI: 10.1098/rspb.2000.1163
|View full text |Cite
|
Sign up to set email alerts
|

Yolk androgens reduce offspring survival

Abstract: Females may favour some offspring over others by differential deposition of yolk hormones. In American kestrels (Falco sparverius), we found that yolks of eggs laid late in the sequence of a clutch had more testosterone (T) and androstenedione (A4) than yolks of first-laid eggs. To investigate the effects of these yolk androgens on nestling 'fitness', we injected both T and A4 into the yolks of first-laid eggs and compared their hatching time, nestling growth and nestling survival with those of first-laid eggs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
192
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 290 publications
(206 citation statements)
references
References 41 publications
12
192
2
Order By: Relevance
“…For example, nestling corticosterone concentrations were higher in American kestrel chicks hatched from androgen-treated than from control eggs (Sockman & Schwabl 2000); similar results were obtained for Japanese quail (Daisley et al 2005). In American kestrels, androgen-exposed chicks also showed reduced growth that may have indirectly led to their higher corticosterone levels or vice versa.…”
Section: Precocial Speciessupporting
confidence: 70%
See 1 more Smart Citation
“…For example, nestling corticosterone concentrations were higher in American kestrel chicks hatched from androgen-treated than from control eggs (Sockman & Schwabl 2000); similar results were obtained for Japanese quail (Daisley et al 2005). In American kestrels, androgen-exposed chicks also showed reduced growth that may have indirectly led to their higher corticosterone levels or vice versa.…”
Section: Precocial Speciessupporting
confidence: 70%
“…Circulating progesterone is associated with onset of broodiness (e.g. Cheng 1979;Sockman & Schwabl 2000). These local intra-ovarian and systemic signalling actions of ovarian steroids in the female have to be considered when proposing adaptive functions for their presence in the egg.…”
Section: Potential Mechanisms (A) How Do Steroids Accumulate In Eggs?mentioning
confidence: 99%
“…In some bird species, androgens deposited in the egg yolk have been found to increase competitive ability of chicks (correlative data in Schwabl, 1993; experimental data in Eising et al, 2001), chick begging (experimental data : Schwabl, 1996;Schwabl and Lipar, 2002;Eising and Groothuis, 2003;Boncoraglio et al, 2006;von Engelhardt et al, 2006) and growth (experimental data: Schwabl, 1996;Eising et al, 2001;Pilz et al, 2004;Navara et al, 2005Navara et al, , 2006Tschirren et al, 2005). In other studies, however, no positive effect of elevated yolk androgens on begging or growth was found (experimental data: Sockman and Schwabl, 2000;Andersson et al, 2004;Pilz et al, 2004;Uller et al, 2005;Saino et al, 2006), or the effect depended on offspring sex (e.g. Saino et al, 2006;Müller et al, 2008;Sockman et al, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…Sex steroids of maternal origin can be found in the egg yolks of many oviparous species (Japanese quail, Adkins-Regan et al, 1995;Zebrafinch, Canary, Cattle egret, American kestrel, Schwabl, 1993, 1996a,b, Schwabl et al, 1997, Sockman and Schwabl, 2000, Whittingham and Schwabl, 2002turtles, Janzen et al, 1998;Zebrafinch, Gil et al, 1999; Dark-eyed junco, Red-winged blackbird, Lipar et al, 1999;damsel fish, McCormick, 1999;Painted turtle, Bowden et al, 2000;Black-headed gull, Eising et al, 2001; Lesser blackbacked gull, Royle et al, 2001;Tree swallow, Whittingham and Schwabl, 2002). It has been suggested that yolk hormone levels correlate with circulating plasma hormone levels in the female (Canary, Schwabl, 1996a) and may vary adaptively with the speciesÕ reproductive strategy and social requirements (Cattle egret, Schwabl et al, 1997, Black-headed gulls: Eising et al, 2001Groothuis and Schwabl, 2002).…”
Section: Introductionmentioning
confidence: 99%